2021. Lost children - Betbeder, Stéphane, 1971- (Titan Comics, 2018)
"It's 2021. Detroit has seceded form the United States and its citizens are under the control of a madman with extraordinary abilities. The only hope of retaking the city lies with four superpowered children. But their powers come with a price -- using them means aging instantly and prematurely. Can they save the city before their powers use up their lives?"--P.4 cover.